RURAL INEQUALITY IN OPPORTUNITIES - A MULTICRITERIAL APPROACH - Tudor Monica, Mihaela (Economics of Agriculture, 2012)
The economic and social inequalities take multiple forms. Their complexity and effect upon individual and overall human development are increasingly deep as several inequality risk sources are cumulated. There is a well-known mutual driving effect that the economic inequality causes have upon social inequality, the reciprocal being also valid. The present study attempts to identify the main inequality sources in the rural area: the territory equipment in the first place, followed by the demographic disequilibria, economic development of the area that provides occupational opportunities, social infrastructure and appetence for investments. We propose a theoretical methodology for the aggregation of rural inequality indicators, which enables grouping the communes from Romania into three clusters, depending on the cumulated intensity of the manifestation of factors that describe and/or condition the socio-economic inequalities.